2017
DOI: 10.3892/ol.2017.6316
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of low dose of celecoxib may be associated with lnc-SCD-1:13 and lnc-PTMS-1:3 but not COX-2 in NCI-N87 cells

Abstract: Abstract. In order to investigate the mechanism of celecoxib and whether long non-coding RNAs (lncRNAs) were involved in the effects of celecoxib treatment in NCI-N87 cells, NCI-N87 cells were treated with 15, 30 and 60 µM celecoxib and an MTT assay was performed to assess cell viability. Following treatment with 15 µM celecoxib, the cell cycle and apoptosis were analyzed by flow cytometry, and the mRNA levels of lnc-SCD-1:13, lnc-PTMS-1:3, cyclooxygenase-2 (COX-2), integrin α3 (ITGA3) and DSH homolog 1 (DVL1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Most of non-coding RNAs disregulations related to doxorubicin, methotrexate and etoposide play a role in chemoresistance exacerbation or inhibition. They are involved in several pathways that regulate cell growth, autophagy, apoptosis and cell proliferation ( 393 – 401 ) or miR-34a ( 105 ), lnc-SCD and lnc-PTMS ( 402 ) modulates the effects of celecoxib. Both doxorubicin and etoposide block DNA replication by topoisomerase II inhibition: thus causing errors in DNA synthesis and promoting apoptosis in cancer cells.…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%
“…Most of non-coding RNAs disregulations related to doxorubicin, methotrexate and etoposide play a role in chemoresistance exacerbation or inhibition. They are involved in several pathways that regulate cell growth, autophagy, apoptosis and cell proliferation ( 393 – 401 ) or miR-34a ( 105 ), lnc-SCD and lnc-PTMS ( 402 ) modulates the effects of celecoxib. Both doxorubicin and etoposide block DNA replication by topoisomerase II inhibition: thus causing errors in DNA synthesis and promoting apoptosis in cancer cells.…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%
“…In the present study, we have demonstrated the many positive effects of the NSAID celecoxib, used at a low dose of 20 mg/kg. It did not come as a surprise that a low dose could have a significant effect in mdx mouse muscles, because treatment with a low celecoxib dose has been shown to be sufficient to have beneficial effects in mice with spinal muscular atrophy by activating survival motor neuron expression and in cancer cells by regulating the cell cycle and apoptosis (56,103). It is important to note that at higher doses, celecoxib treatment can have damaging side effects, such as increased likelihood of cardiovascular thrombotic events and liver and gastrointestinal lesions (88,104,105).…”
Section: Repurposing Celecoxib For the Treatment Of Dmdmentioning
confidence: 99%